FORMS OF STUDENTS LANGUAGE POLITENESS IN SOCIAL MEDIA: PREPARATION SCHOOL POLICIES ON COMMUNICATION ETHICS - Isnaini, Ruswi; Sudiyana, Benedictus; Pratiwi, Veronika Unun (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe  politeness compliance, politeness violation, factors causing students' language impoliteness in WhatsApp communication, and drafting a digital communication ethics policy. The method used is a descriptive qualitative case study approach on students in grades 4-6 at SD Negeri 03 Lalung. Data will be in the form of excerpts of speech in WhatsApp, questionnaire responses, and interviews. The source of data is screenshots of WhatsApp group conversations. The results show the dominance of the maxims of agreement and tact, but violations occur due to direct criticism, inability to control emotions, and harsh diction. Policies include integrating digital communication ethics in learning, developing digital politeness-based teaching materials, and mentoring teachers.